Quantifying the consequence of applying conservative assumptions in the assessment of oil spill effects on polar cod (Boreogadus saida) populations - de Vries, Pepjin; Tamis, Jacqueline; Nahrgang, Jasmine; Frantzen, Marianne; Jak, Robbert; Klok, Chris; van den Heuvel-Greve, Martine J; Hemerik, Lia (Polar Biology, 2021)
In order to assess the potential impact from oil spills and decide the optimal response actions, prediction of population level effects of key resources is crucial. These assessments are usually based on acute toxicity data combined with precautionary assumptions because chronic data are often lacking. To better understand the consequences of applying precautionary approaches, two approaches for assessing population level effects on the Arctic keystone species polar cod ( Boreogadus saida ) were compared: a precautionary approach, where all exposed individuals die when exposed above a defined threshold concentration, and a refined (full-dose-response) approach. A matrix model was used to assess the population recovery duration of scenarios with various but constant exposure concentrations, durations and temperatures. The difference between the two approaches was largest for exposures with relatively low concentrations and short durations. Here, the recovery duration for the refined approach was less than eight times that found for the precautionary approach. Quantifying these differences helps to understand the consequences of precautionary assumptions applied to environmental risk assessment used in oil spill response decision making and it can feed into the discussion about the need for more chronic toxicity testing. An elasticity analysis of our model identified embryo and larval survival as crucial processes in the life cycle of polar cod and the impact assessment of oil spills on its population.